ANTIOXIDANTS, BIOCHEMICAL, AND HEMATOLOGICAL PARAMETERS CHANGE IN WORKERS OCCUPATIONALLY EXPOSED TO RADON INHALATION AT CERTAIN CONSTRUCTION MATERIAL INDUSTRIES IN ERBIL, IRAQ - Othman, Sardar Q.; Mohammed, Sarbaz I.; Ahmed, Ali H. (Science Journal of University of Zakho, 2024)
This study examined the effects of radon on the endogenous antioxidants, biochemical, and hematological parameters of workers in Erbil, Iraqi Kurdistan. This was carried out to ascertain how radon affects the health of those who work in certain factories producing building materials. The case study group consisted of 70 workers, who were then divided into seven subgroups (gypsum, cement plant, lightweight block, marble, red brick 1, crushed stone, and concrete block 2), while the control group consisted of 20 healthy volunteers. The total antioxidant capacity (TAC), levels of carcinoembryonic antigen (CEA), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX), the complete blood count (CBC), and liver function tests were evaluated. The statistical analysis revealed that the antioxidant activities and CEA levels between the case study group and the control group differed significantly. Also, antioxidant enzyme activities and indoor radon concentration, the annual effective dosage, were found to be highly significantly correlated by Pearson and Spearman analyses in the case study group. Additionally, the results demonstrated a substantial correlation in the data between the levels of CEA biomarkers and radon (r=0.478, p˂0.000). The present results showed that radon concentration increased alanine aminotransferase (ALT) activity in a radon concentration-dependent manner (r=0.263 and p ˂0.05). The aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total bilirubin activities, on the other hand, were not significantly affected by radon. The most significantly influenced CBC parameter was the low white blood cells (WBC) in the case study group compared to the controls. Low platelet count (PLT) was the second-highest problematic metric. The other CBC values, however, did not significantly differ between the research group and the control group. This study offers a preliminary image of the endogenous antioxidant systems in employees, especially to show a connection between radon and the occurrence of cancer among workers in Iraq Kurdistan Region.